Involvement of anterior and posterior corneal surface area imbalance in the pathological change of keratoconus. Issue 1 (December 2018) - Kitazawa, Koji; Itoi, Motohiro; Yokota, Isao; Wakimasu, Koichi; Cho, Yuko; Nakamura, Yo; Hieda, Osamu; Kinoshita, Shigeru; Sotozono, Chie
Abstract Keratoconus (KC) is an ectatic disorder with a high prevalence rate. However, the exact cause of the disease and possible underlying mechanisms of development remain unclear. In this present study, we aimed to investigate the anterior and the posterior corneal surface area in normal, forme fruste keratoconus (FFKC), and keratoconic eyes (as a reference group) using anterior segment optical coherence tomography (AS-OCT) in order to assess the pathological change of KC. The surface areas of the anterior or posterior cornea, and the anterior-posterior (As/Ps) ratio of corneal surface area, were measured at the central 5.0 mm-, 6.0 mm-, and 7.0 mm-diameter areas via AS-OCT, and a comparison between the normal eyes and FFKC eyes was then performed using the Mann-Whitney U test. The posterior surface area at the central 5.0 mm areas in the FFKC eyes (20.430 mm2 ) and KC eyes (20.917 mm2 ) seemed to become larger than that of normal eyes (20.389 mm2 ) (normal vs FFKC;P = 0.06). Moreover, the As/Ps of the corneal surface area in the FFKC eyes (0.986) and the KC eyes (0.976) was significantly smaller than that of the normal eyes (0.988) (normal vs FFKC;P < 0.01). Anterior and posterior corneal surface area imbalance may reflect keratoconic eyes at the early stage of the disease.